2022
DOI: 10.1155/2022/5188703
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Effect of Percutaneous Cone Shaping in Patients with Osteoporotic Vertebral Fractures

Abstract: Objective. To study and analyze the clinical effect of percutaneous cone shaping in patients with osteoporotic vertebral fractures. Methods. A total of 100 patients with vertebral osteoporotic fracture treated in our hospital from June 2019 to September 2020 were selected, and there were 50 patients with vertebral osteoporotic fracture in each group. Patients could be divided into two groups according to different treatment plans: one group was vertebroplasty patients for group A, and the other group was nonsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%